THE EFFECT OF AUDIT COMMITTEE EFFECTIVENESS AND AUDIT QUALITY ON EARNINGS MANAGEMENT - Jannah Zahra Inayah; Andrian Budi Prasetyo (Riset Akuntansi Keuangan, 2020)
This study examines the effect of audit quality and audit committee effectiveness on earnings management in manufacturing company with effectiveness of audit committee as moderating variable. This study uses 300 samples from manufacturing company listed on the Indonesian Stock Exchange during the period of 2016-2018, and it is determined by using purposive sampling method. The data used in this study is secondary data which contains company financial information and annual reports obtained from Indonesia Stock Exchange (IDX) and Bloomberg. This research is using multiple regression analysis as data analysis technique. The result shows that there is a significant negative effect towards the specialization of auditors moderated by audit committee on earnings management. However, the auditor's reputation moderated by the audit committee has a positive and significant effect, and the period of auditor moderated by the audit committe